PENGARUH ARAH DAN KETEBALAN IRISAN KUNYIT TERHADAP SIFAT FISIK TEPUNG KUNYIT YANG DIHASILKAN - Priastuti, Rita Catur; -, Tamrin; Suhandy, Diding (The University of Lampung, 2016)
The purpose of this research was to evaluate the influence of the direction and thickness of turmeric slice on thephysical powder of turmeric powder. The treatments were two different of treatments cut vertical slices (cut fiber),horizontal (unidirectional fibers) and cut with three thicknesses (0.3 cm, 0.6 cm, and 0.9 cm). The measuredparameter were water content, angle of repose, fineness modulus, uniformity index, grain yield, bulk density, andthe flour color. The water content obtained wasn’t reached the Indonesia Standard Nasional which is still below12%, while the angle of repose has been good angle with the value 31°-41°. The fineness modulus as much as4.02% - 4.66%. Uniformity index grains with rough category has the highest amount than with the percentageof medium and smooth category, and the medium category on average direction of a cut fiber have percentagegreater than the unidirectional fiber although the difference is only a little. The percentage is still low grain yield<50%. Bulk density values obtained in this research ranged between 354.89 - 386.90 kg / m 3 . The resulting colorwasn’t much different and still in the desired category was yellow-orange. Different parameters affect the slicethickness uniformity index and grain yield of turmeric. The thicker slices of turmeric, then the index uniformityand yield of turmeric powder granules produced higher. Different directions slices and slice thickness differencedoes not affect the water content, angle of repose, fineness modulus, bulk density, and color of turmeric powder.Keywords: turmeric powder, slicesdirection, slice thickness, water content , angle of repose, bulk density.